HPMA copolymer-bound doxorubicin targeted to tumor-specific antigen of BCL1 mouse B cell leukemia - Kovár, M; Mrkvan, T; Strohalm, J; Etrych, T; Ulbrich, K; Stastný, M; Ríhová, B (Journal of controlled release, 2003)
N-(2-Hydroxypropyl)methacrylamide (HPMA) copolymer carrier containing the anticancer drug doxorubicin and targeted with B1 monoclonal antibody (mAb) to BCL1 leukemia cells was synthesised and tested in vitro and in vivo. BCL1 leukemia growing in syngenic Balb/c mice was selected as a tumor model system. B1 mAb recognising the idiotype of surface IgM on BCL1 cells was used as a targeting moiety. Both B1 mAb and doxorubicin were conjugated to HPMA copolymer carrier by aminolysis through a tetrapeptidic Gly-Phe(D,L)-Leu-Gly spacer to ensure the intracellular delivery and controlled release of the drug. B1 mAb-targeted conjugate was shown to possess strictly tumor-specific binding capacity to target BCL1 cells in vitro. A similar conjugate, but containing human nonspecific Ig (HuIg) instead of B1 mAb, failed to bind to BCL1 cells. In vitro, B1 mAb-targeted conjugate demonstrated 40-fold higher cytotoxic effect than nontargeted or human nonspecific Ig-containing HPMA copolymer-bound doxorubicin. Conjugate targeted with B1 mAb was also shown to bind to target BCL1 cells in vivo. B1 mAb-targeted conjugate was shown to be more efficient in the treatment of established BCL1 leukemia than free doxorubicin, nontargeted and human nonspecific Ig-containing conjugate. Antibody-targeted polymeric drugs are thus promising conjugates for cancer treatment.
Keywords: protilátky anti-idiotypické; doxorubicin; monoklonální protilátky; imunokonjugáty; slezina; Survival Rate; Cell Line, Tumor; leukocyty mononukleární; Hydrogels; Doxorubicin; Acrylamides; antigeny nádorové; Leukemia, B-Cell; myši inbrední BALB C; Immunoconjugates; Inhibitory Concentration 50; buněčné dělení; Reticulocyte Count; hydrogely; Flow Cytometry; Mice, Inbred BALB C; Body Weight; Spleen; injekce intravenózní; Drug Delivery Systems; průtoková cytometrie; Animals; Injections, Intravenous; Cell Division; Leukocytes, Mononuclear; injekce intraperitoneální; Injections, Intraperitoneal; zvířata; Antigens, Neoplasm; akrylamidy; myši; Antibodies, Anti-Idiotypic; inhibiční koncentrace 50; Antibodies, Monoclonal; nádorové buněčné linie; Mice; tělesná hmotnost; lékové transportní systémy; míra přežití; leukemie B-buněčná; počet retikulocytů